Guidance Counselors’ experiences on policy changes, counseling students from immigrant backgrounds and time management - Cano, Ana Ciaran (2022)
This qualitative research explores guidance counselors’ experiences and challenges on 4 areas of their profession: Policy reforms, interaction with students and factors they consider important in their counseling roles. Lastly, in sections 3 and 4, their perspectives on counseling students from immigrant backgrounds. This study has two goals; To contribute to the research and development of counseling services for students from immigrant backgrounds and, to explore guidance counselors’ views on the challenges they face in hopes of raising awareness. 13 guidance counselors from southern and central Finland were surveyed and/or interviewed. The data was analyzed using thematic analysis from a narrative perspective approach. Results indicate that the participating guidance counselors see that their jobs have become more demanding due to policy changes, administrative implementation, increasingly diverse student body, and the counselor-to-student ratio which has remained consistently high. Time management was identified as a problem affecting specifically the completion of essential and critical tasks. These tasks were also reported by guidance counselors as being the most enjoyable. Communication difficulties attributed to language differences and mismatched expectations between students, their families, and the guidance counselors were also a theme.Previous research supports my findings. The stakeholders are addressing the issues above mentioned.